Розподiл електричної активної потужностi окремого електроспоживача на дiлянках енергосистеми - Пiвняк, Г. Г.; Волков, О.В.; Мирошниченко, О. Г. (Видавничий дім "Академперіодика" НАН України, 2007)
The dependences that characterize the separate energy-consumer active electric power distribution in different parts of the energy system are obtained.